Primary Amenorrhea in Anorexia Nervosa: Impact on Characteristic Masculine and Feminine Traits. (3rd October 2013) - Baker, Jessica H.; Sisk, Cheryl L.; Thornton, Laura M.; Brandt, Harry; Crawford, Steven; Fichter, Manfred M.; Halmi, Katherine A.; Johnson, Craig; Jones, Ian; Kaplan, Allan S.; Mitchell, James E.; Strober, Michael; et al.
Abstract Animal studies indicate that gonadal hormones at puberty have an effect on the development of masculine and feminine traits. However, it is unknown whether similar processes occur in humans. We examined whether women with anorexia nervosa (AN), who often experience primary amenorrhea, exhibit attenuated feminization in their psychological characteristics in adulthood due to the decrease/absence of gonadal hormones at puberty. Women with AN were compared on a number of psychological characteristics using general linear models on the basis of the presence/absence of primary amenorrhea. Although women with primary amenorrhea exhibited lower anxiety scores than those without primary amenorrhea, in general, results did not provide evidence of attenuated feminization in women with AN with primary amenorrhea. Future research should utilize novel techniques and direct hormone measurement to explore the effects of pubertal gonadal hormones on masculine and feminine traits. Copyright © 2013 John Wiley & Sons, Ltd and Eating Disorders Association.